Imaging features and diagnosis of tuberculosis of the breast. Issue 3 (March 2017) - Longman, C.F.; Campion, T.; Butler, B.; Suaris, T.D.; Khanam, A.; Kunst, H.; Tiberi, S.; O'Keeffe, S.A.
Abstract : Aim: To outline the pathophysiology, clinical presentation, imaging features, and relevant investigations of the different subtypes of breast tuberculosis (TB). Materials and methods: A review was undertaken of all cases (33 in total) of breast TB presenting to Barts Health NHS Trust within a 10-year period, including patient demographics, imaging features, and route of diagnosis. Results: Thirty-three cases of proven granulomatous TB of the breast were identified (11 mastitis obliterans, 10 nodular caseous form, five sclerosing form, four disseminated disease, and three abnormal axillary lymph nodes). No cases of miliary breast TB were identified. Fine-needle aspiration cytology aided diagnosis in six patients (<20% of cases); however, the majority of patients required further investigation; namely core biopsy. Over a third of patients (12/33) had multiple clinic attendances prior to diagnosis. Mean delay in diagnosis was 3.7 months (median 0 months, IQR= 3). Conclusion: Breast TB is a rare challenging diagnosis with a wide range of imaging features. Core biopsy is essential for definitive diagnosis. A multidisciplinary approach involving surgeons, radiologists, TB consultants, and microbiologists is required, coupled with a high index of clinical suspicion in order to aid timely diagnosis, and initiate prompt treatment to reduce complications. Highlights: TB of the breast should be considered in all patients presenting with an abscess or atypical mass. Risk factors include females of reproductive age, multiparity and HIV co-infection. There are 5 subtypes of breast TB with differentiating radiological features. Ultrasound followed by core biopsy and TB culture is advocated to establish diagnosis. We propose a diagnostic pathway to increase awareness of breast TB, enable prompt diagnosis and reduce complications.